2014
DOI: 10.1002/ejoc.201402406
|View full text |Cite
|
Sign up to set email alerts
|

Merrilliadione – a Rare Isopropyl (13→11)‐abeo‐9,11‐seco Abietane Diterpene from Illicium merrillianum

Abstract: Merrilliadione (1), a new diterpene with a unique isopropyl (13Ǟ11)-abeo-9,11-seco-abietane skeleton, and two new abietane diterpenoids (2 and 3) were isolated from Illicium merrillianum. This is the first report of an isopropyl (13Ǟ11)-[a]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The isolated compounds ( 1–11 ) were evaluated for cytotoxic activity against human tumor cell lines A549 (non-small-cell lung cancer cells), HCT116 (human colon cancer cells), MDA-MB-231 (human breast cancer cells), and HepG2 (human hepatocellular carcinoma cells) in vitro (Table 3). 39 The results showed that compounds 1 and 2 displayed appreciable cytotoxic activity against A549 and HCT116 cell lines with IC 50 values of 6.40–7.76 μM, whereas compounds 9 and 10 only exhibited potent inhibition against A549, HCT116 and HepG2 cells with IC 50 values of 9.46–15.07 μM. Doxorubicin was employed as the positive control and its IC 50 values against A549, HCT116, MDA-MB-231 and HepG2 cells were 0.18 ± 0.004, 0.07 ± 0.001, 0.59 ± 0.010 and 0.06 ± 0.001 μM, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The isolated compounds ( 1–11 ) were evaluated for cytotoxic activity against human tumor cell lines A549 (non-small-cell lung cancer cells), HCT116 (human colon cancer cells), MDA-MB-231 (human breast cancer cells), and HepG2 (human hepatocellular carcinoma cells) in vitro (Table 3). 39 The results showed that compounds 1 and 2 displayed appreciable cytotoxic activity against A549 and HCT116 cell lines with IC 50 values of 6.40–7.76 μM, whereas compounds 9 and 10 only exhibited potent inhibition against A549, HCT116 and HepG2 cells with IC 50 values of 9.46–15.07 μM. Doxorubicin was employed as the positive control and its IC 50 values against A549, HCT116, MDA-MB-231 and HepG2 cells were 0.18 ± 0.004, 0.07 ± 0.001, 0.59 ± 0.010 and 0.06 ± 0.001 μM, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The cytotoxicity of compounds against human non-small-cell lung carcinoma cells (A549), human colon cancer cells (HCT116), human breast cancer cells (MDA-MB-231), and human hepatocellular carcinoma cells (HepG2) was determined by MTT assay. 39 The assay was performed in triplicate. All cells were seeded in 96-well plate at a density of 10 4 cells per well and incubated in a humidified 5% CO 2 atmosphere at 37 °C for 24 h. Then the medium was removed, and each well was treated with 50 μL of medium containing 0.2% DMSO (control group), or 1–100 μM tested compounds, or the positive control doxorubicin.…”
Section: Methodsmentioning
confidence: 99%
“…Further abietanes including some glycosides have been isolated from Lycopus lucidus, 73 Clerodendrum bungei, 74,75 and C. trichotomum. 76 seco-Abietanes such as merrilliadione (a 9,11-secoabietane) 77 and wardinol A (a 9,10 seco-abietane) 78 have been obtained from Illicium merrillianum and I. wardii respectively. Examination 79 of the trunk of Abies holophylla (Pinaceae) yielded a pinacolic rearrangement product holophyllin A 16 whilst a spiro-lactone structure 17 has been assigned 80 to decandrinin which was obtained from the mangrove plant, Ceriops decandra.…”
Section: Abietanesmentioning
confidence: 99%